Antimicrobial and antioxidant activities of mixed methanol extract of Aloe Vera, Hibiscus flower and Ati-Ati leaves / Nur Amira Mohd Amin and Ida Muryany Md Yasin - Mohd Amin, Nur Amira; Md Yasin, Ida Muryany (UiTM Cawangan Negeri Sembilan, 2023)
Nowadays, modern medication always used synthetic drugs which will cause many bad effects and ignoring the safe medication such as herb plants that possess antimicrobial and antioxidant properties. The aim of the study is to evaluate the antimicrobial activity and to determine antioxidant assay of mixed methanol extract of Aloe Vera, Hibiscus flowers and Ati-ati leaves. The antimicrobial activity involved disk diffusion assay and the antioxidant activity is using DPPH radical scavenging assay. The concentration of mixed extract used were 500 mg/ml, 250 mg/ml, 100 mg/ml and 50 mg/ml. From the result of antibacterial activity, Klebsiella pneumoniae and Escherichia coli have higher inhibition zones than Bacillus cereus and Bacillus subtilis which are 22.33 mm and 16 mm respectively at higher concentration of extract, 500 mg/ml. For the antifungal activity, Candida albicans showed the highest inhibition zones than Rhizopus oligosporus and Rhizopus stolonifer which 13.66 mm at the highest concentration of the mixed extract. For the antioxidant activity, the highest concentration which 500 mg/ml have highest radical scavenging that is 93.31% while for the other concentration 250, 100 and 50 mg/ml contain 73.00%, 36.67% and 7.82% respectively of radical scavenging activity. As conclusion, mixed methanol extract of Aloe Vera, Hibiscus flowers and Ati-ati leaves have ability to conduct antimicrobial and antioxidant activity against pathogenic microbe tested.